Googly eyes and yard signs: Deconstructing one professor’s successful rebuffing of a right-wing attack on an academic institution - Catalano, Theresa and Kohen, Ari (Discourse & Society, 2020)
Right-wing populism is on the rise worldwide, and political attacks against universities have increased in the United States since the election of Donald Trump. In 2017, an incident occurred at the University of Nebraska–Lincoln which resulted in accusations of hostility toward conservative students. Just over a year later, political forces again attempted to denigrate the university’s reputation, but this time they did not succeed. This (multimodal) positive discourse analysis/generative critique combines collaborative auto-ethnography to describe the way these events were represented in the media, deconstructing a professor’s methods of countering a right-wing attack on an academic institution. Findings demonstrate the use of multiple strategies such as controlling the narrative through social media savvy; using linguistic strategies such as refutation of strawman fallacies, syntax, deixis and emotional appeal; and use of image.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wOTU3OTI2NTE5ODgwMDM3